2011
DOI: 10.1002/jcp.22494
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide sensitizes hepatocellular carcinoma cells to trail by inducing the expression of death receptors through inhibition of STAT3 activation

Abstract: This article shows that HepG2, Hep3B, and SK-Hep1 cells, three lines of human hepatocellular carcinoma (HCC) cells, are resistant to apoptosis induced by tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Parthenolide, a sesquiterpene lactone found in European feverfew, has been shown to exert both anti-inflammatory and anti-cancer activities. This article demonstrates that co-treatment with parthenolide and TRAIL-induced apoptosis with synergistic interactions in the three lines of HCC cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 52 publications
2
71
0
Order By: Relevance
“…Previous it was reported that a decrease in the phosphorylated form of STAT3 could be responsible for the enhanced expression of death receptor (25). In this study, we found that bufotalin together with TRAIL inhibited STAT1 and STAT3 phosphorylation, and induced DR5 mRNA and protein expression, indicating that bufotalin may enhance TRAIL-induced death receptor expression through STAT3.…”
Section: Discussionsupporting
confidence: 53%
“…Previous it was reported that a decrease in the phosphorylated form of STAT3 could be responsible for the enhanced expression of death receptor (25). In this study, we found that bufotalin together with TRAIL inhibited STAT1 and STAT3 phosphorylation, and induced DR5 mRNA and protein expression, indicating that bufotalin may enhance TRAIL-induced death receptor expression through STAT3.…”
Section: Discussionsupporting
confidence: 53%
“…Recent publications suggest that parthenolide-mediated effects on death receptors depend on a reduction in levels of phosphorylated and active forms of STAT proteins [41], which may be due to an inhibitory effect of PN on activation of JAK proteins. Among important members of the TNF family, the TNF-related apoptosis-inducing ligand (TRAIL), also known as the Apo-2 ligand, is found to interact with five distinct TRAIL receptors [42,43].…”
Section: Parthenolide-mediated Stat Inhibitionmentioning
confidence: 99%
“…Twenty-four hours after seeding, cells were treated with drugs for the time indicated in the Results. Cell viability was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay as previously reported (16). MTT is reduced to purple formazan in the mitochondria of living cells.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%